Rancang Bangun Fetal Doppler Simulator untuk Kalibrasi Fetal Doppler - Pramudya mahardhika; Abdul Haris Kuspranoto; Muhammad Ulin Nuha ABA (LPPM POLBITRADA, 2025)
The Fetal Doppler Simulator for calibration is a device designed to ensure the accuracy and reliability of Fetal Doppler equipment in monitoring fetal heart rate. Traditionally, calibration of Fetal Doppler devices has relied on limited methods with relatively high costs. Therefore, an alternative calibration medium that is more economical, practical, and reliable is needed. This simulator functions by generating fetal heartbeat signals with various rhythm patterns, ranging from normal conditions to pathological variations such as tachycardia and bradycardia. The research method applied was Research and Development (R&D), which included needs analysis, design planning, feature integration, prototype construction, and performance testing. The test results showed that the Fetal Doppler Simulator was able to generate stable heartbeat simulations with measurement values that remained within acceptable tolerance limits (≤5%). Based on these findings, it can be concluded that the development of this Fetal Doppler Simulator is feasible and effective as a calibration medium. This research is expected to offer a practical alternative for healthcare facilities to perform Fetal Doppler calibration at a lower cost.